POLITIK MULTIKULTURAL ETNIS TIONGHOA PASCA-REFORMASI DI KOTA MEDAN - Deny Setiawan (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2013)
This research proposed to get a factual description about multicultural politics of Chinese at post-reform in Medan. Factuality multicultural politics explored through the perspective of Chinese leaders thinking about the themes reconceptualization of integration and reconstruction of national identity. Empirical data of the two themes, used as input in the development of a multicultural society project in Medan. Collection of data was performed by assessment techniques documentation, observation and interviews. Data analysis using analytic comparison that in the data processing included in the method of agreement and method of difference. The research findings indicate (1) the perspective thinking of the Chinese leaders in reconceptualization of integration leads to the choice of